Prediction of Remaining Life of Transformer at PLTU Suralaya Unit 6 Using Tan Delta Method at 1 mHz and Degree of Polymerization Calculation - Yusrizal, Amri; Abiyasa, Agus Putu; Suriana, I Wayan; Adrama, I Nyoman Gede (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Assessing the insulation condition of power transformers is crucial for maintaining the reliability of electrical power systems. This research aims to predict the remaining life of the transformer at PLTU Suralaya Unit 6 by integrating the measurement of the dissipation factor (tan δ) using Dielectric Frequency Response (DFR) testing at ultra-low frequency (1 mHz = 0.001 Hz) and estimating the Degree of Polymerization (DP) through empirical correlation. The DFR measurements were performed with the OMICRON DIRANA device (frequency range 0.1 mHz–1 kHz) and validated against tan δ measurements at 50 Hz using OMICRON CPTD equipment. The dissipation factor at 1 mHz was extracted and converted to an estimated DP value through a validated regression model. Results show a DP value of approximately 302, indicating advanced degradation of the cellulose insulation. This corresponds to an estimated remaining life percentage of 29.68%, equivalent to an operational lifespan of roughly 11.87 years before reaching the end-of-life threshold. The study confirms that ultra-low-frequency DFR testing combined with DP estimation provides a non-destructive and effective approach for transformer remaining life prediction. It is recommended to implement condition-based monitoring and supplement with oil chemical analysis (e.g., furan compounds) and other diagnostic methods to enhance prediction accuracy and support proactive asset management.